Twenty-one Years of Mediation: How Should We Appraise the Development of Mediation within Singapore? - QUEK ANDERSON, Dorcas (Institutional Knowledge at Singapore Management University, 2015)
The year 2016 marks the 40th anniversary of the 1976 Pound Conference, a conference that has been widely regarded as one of the defining moments in the alternative dispute resolution movement. The International Mediation Institute (“IMI”) is currently organising the international 2016–2017 Global Pound Conference Series to commemorate the Pound Conference and to take the opportunity to appraise the current state of ADR. For Singapore, with a shorter ADR history of around 20 years, this is an opportune time for the mediation community to collectively appraise the gains as well as gaps in the development of mediation. This article examines a poll of mediators conducted at a mediation forum entitled "A Joint Session for Mediators - Discussing What is Close to the Heart of Mediators" in the State Courts in March 2015. It discusses the progress made in the last five years made in increasing the use of mediation within Singapore and the crucial areas to focus on in the growth of mediation. In addition, it proposes that regulation of the mediation profession be a responsibility owned by the entire industry, as well as cautions against focusing excessively on setting standards at the expense of creating a community of mediators with a culture of continual improvement.